Rancang Bangun Aplikasi Pengawasan Dan Pengendalian Komputer Laboratorium Multimedia STMIK Palangkaraya - Sam’ani Sam’ani; Syarifah Annisa; Heri Heri (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
The progress of technology and computer surveillance systems at this time has provided a significant positive contribution in all fields to support and improve the performance of a system. One of the technological advances in the field of computers is computer monitoring and control. Computer monitoring and control systems used in computer laboratories at the College of Information and Computer Management (STMIK) Palangkaraya still use a paid system or must first purchase to be able to use it in every computer laboratory room, so that not all computer laboratory rooms can be monitored using the system because there are not a few costs to purchase the system. Therefore, to supervise all the STMIK Palangkaraya laboratory rooms, a computer monitoring and control system is built that can be used free of charge. The software development method used is the System Development Life Cycle (SDLC) method with a waterfall model development approach. The programming language used is Microsoft Visual Basic. Based on the results of tests on the system that was built to produce all the processes and facilities contained in the system running in accordance with the test items that have been set.